Geoinformatics-based assessment of land degradation and ecological recovery (2004-2024) in the Phung River Basin, Northeast Thailand - Ruksajai, Narathip; Saraphirom, Phayom; Lohpaisankrit , Worapong (Journal of Degraded and Mining Lands Management, 2025)
A geoinformatics-based assessment of land degradation and early ecological recovery was conducted in the Phung River Basin, Northeast Thailand between 2004 and 2024. Multi-temporal Landsat imagery, NDVI-based vegetation indices, and centimeter-level UAV RTK GNSS ground validation were integrated to detect land cover changes and ecological dynamics. Significant declines in cropland and forest areas were observed, largely due to urbanization and the expansion of plantations. Localized NDVI improvements suggested early signs of vegetative regeneration. The integrated classification framework achieved high accuracies—93.4% in 2004 and 86.9% in 2024—validating its robustness for land transformation analysis. The findings of this study contribute to landscape monitoring practices and provide actionable insights for policymakers to achieve SDG 15.3 on land degradation neutrality.